Rencana Strategis Transformasi Teknologi Informasi pada Industri Kelapa Sawit Menggunakan Framework Zachman - Solihin, Indra Permana; Triwahyono, Bambang; Wibisono, Mohamad Bayu; Munir, Sirojul (Jurnal Teknologi Terpadu, 2024)
This research aims to design and implement an effective Information Technology (IT) Transformation Strategic Plan to increase national palm oil productivity in the palm oil industry. IT strategies will be developed using the Zachman Framework, considering architectural aspects and business perspectives. This research was carried out from February to October 2024 at UPNVJ’s Data Science laboratory and company facilities in Jakarta and Central Kalimantan. This research contributes to integrating the Zachman Framework with a specific information technology transformation approach for the palm oil industry, which has not been widely applied in the previous literature. The implementation step involves an in-depth analysis of business needs and processes and the development of appropriate IT solutions. The research results are expected to result in significant transformations in palm oil industry operations, such as increased productivity, efficiency, and adaptation to market changes. The study also considers architectural dimensions and business perspectives in implementing effective IT solutions. Cooperation with key stakeholders, including palm oil producers, suppliers, and consumers, is highly valued. This study’s results are expected to guide other industries and the government in formulating policies supporting IT transformation in the national palm oil industry sector.